2022
DOI: 10.1021/acsnano.2c09115
|View full text |Cite
|
Sign up to set email alerts
|

Water Structures Reveal Local Hydrophobicity on the In2O3(111) Surface

Abstract: Clean oxide surfaces are generally hydrophilic. Water molecules anchor at undercoordinated surface metal atoms that act as Lewis acid sites, and they are stabilized by H bonds to undercoordinated surface oxygens. The large unit cell of In2O3(111) provides surface atoms in various configurations, which leads to chemical heterogeneity and a local deviation from this general rule. Experiments (TPD, XPS, nc-AFM) agree quantitatively with DFT calculations and show a series of distinct phases. The first three water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…These two new peaks were up-shifted by 1.1 eV from the peak position of the In 2 O 3 reference (red dashed line). 75 Furthermore, a strong phosphorus signal was detected in samples intercalated with P 2 O 5 (Figure 6b). Therefore, based on these observations, we can exclude the formation of In 2 O 3 in the P 2 O 5 intercalated samples.…”
Section: ■ Results and Discussionmentioning
confidence: 97%
“…These two new peaks were up-shifted by 1.1 eV from the peak position of the In 2 O 3 reference (red dashed line). 75 Furthermore, a strong phosphorus signal was detected in samples intercalated with P 2 O 5 (Figure 6b). Therefore, based on these observations, we can exclude the formation of In 2 O 3 in the P 2 O 5 intercalated samples.…”
Section: ■ Results and Discussionmentioning
confidence: 97%
“…The In 3d spectrum demonstrates the presence of In 3þ in the hydrogel. [23,24] These high-valence metal ions can be served as sorption sites to couple with nitrogen or oxygen atoms. This coupling method belongs to chemisorption, the empty electron orbitals of metallic and the lone electron pairs of nonmetallics comprise the chemical bond.…”
Section: Resultsmentioning
confidence: 99%
“…14 The absence of a strongly shifted peak in the O 1s XPS spectra supports the assessment that only dissociated water is present on the surface and is in agreement with the previous STM study of water on In 2 O 3 (111), which showed that it is possible to achieve a coverage of three water molecules per In 2 O 3 (111) unit cell at room temperature. 19,44 Methanol and Formic Acid on Stoichiometric In 2 O 3 (111). To study how the methanol product and possible reaction intermediate formic acid bind to the surface, their adsorption on stoichiometric In 2 O 3 (111) was studied experimentally and computationally.…”
Section: Methodsmentioning
confidence: 99%